2009
DOI: 10.1111/j.1439-0388.2009.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL for porcine muscle fibre traits in a White Duroc × Erhualian F2 resource population

Abstract: Muscle fibre traits are related with meat quality in meat animals. In this study, a whole-genome scan with 183 microsatellite markers covering the pig genome was performed to identify quantitative trait loci (QTL) for cross-sectional area, numerical percentage and relative area of type I, IIA and IIB myofibres, fibre number per square centimetre and total fibre number in the longissimus muscle by using 120 F(2) animals in a White Duroc x Erhualian intercross. In total, 20 QTL were mapped on pig chromosomes (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…In our previous study, the following QTLs were identified within the same sample population: 3 QTLs associated with IIB_A on SSC7, SSC8, and SSC15; 3 QTLs associated with IIA_A on SS7 and SSC11; 1 QTL associated with FN on SSC7; and 1 QTL associated with I_NP on SSCX. The confidence interval for these QTLs ranged between 11 and 127 cM [10]. Interestingly, fewer QTLs and no consistent QTLs were detected in the present GWAS study compared with previous studies.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…In our previous study, the following QTLs were identified within the same sample population: 3 QTLs associated with IIB_A on SSC7, SSC8, and SSC15; 3 QTLs associated with IIA_A on SS7 and SSC11; 1 QTL associated with FN on SSC7; and 1 QTL associated with I_NP on SSCX. The confidence interval for these QTLs ranged between 11 and 127 cM [10]. Interestingly, fewer QTLs and no consistent QTLs were detected in the present GWAS study compared with previous studies.…”
Section: Discussioncontrasting
confidence: 79%
“…These 11 traits included area (A), relative area (RA), and numerical percentage (NP) of the three types of myofibers (I, IIA, and IIB) and FN and FTN. This approach was based on previous study that measured muscle fiber traits [1,10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical approach to dissecting the genetic architecture is linkage analysis. Quantitative trait locus mapping for traits related to loin muscle and muscle fiber composition via microsatellites markers has been reported in Japanese Wild Boar × Large White (Nii et al, 2005), Duroc × Berlin Miniature Pig (Wimmers et al, 2006(Wimmers et al, , 2007, Iberian × Landrace (Estellé et al, 2008) and White Duroc × Erhualian (Li et al, 2009). Although microsatellite-based genetic linkage mapping is valuable to discuss the common genetic loci across breeds or within breeds, it is limited by the low resolution.…”
Section: Den T I F Icat Ion Of Gen Et Ic Loc I a S Soc I At Ed W I T ...mentioning
confidence: 99%